ZOONOTIC AND HISTO-PATHOLOGICAL ASPECTS OF VARIOUS TOXOPLASMA GONDII STRAINS IN FEMALE RATS - El Fadaly, Hasan; Soror, Ashraf; Barakat, Ashraf; Abd El-Razik, khaled (African Journal of Infectious Diseases (AJID), 2015)
Background: Toxoplasma gondii is one of the most opportunistic zoonotic protozoan, typifying three virulent types; I, II, and III; with possible characteristic pathological and serological aspects, showing zoonotic and reproductive impact. The present investigation dealt with the concept, and focused on studying the susceptibility of female rats to cerebral and uterine toxoplasmosis, with reference to diversity of T. gondii virulent types through histo-pathological and serological assays. Materials and Methods: A total of thirty pathogen free Sprague-Dawley female rats were used for the study. They were divided into two main groups (acute and chronic) groups: Both were further subdivided into three additional subgroups in correspondence with the three T. gondii types; I, II and III (local isolates) strains. ELISA IgM / IgG as well as pathological investigations of visceral organs; brain and muscles were done prior to 7 days post Inoculation. (DPI) and 35 DPI, represent the acute and chronic stages respectively. Results: The results revealed that type I possess, a higher percentage for inducing cerebral and uterine toxoplasmosis in addition to higher elevation of both parasite load and immunoglobulin titers; while cystogenic types II and III showed lower values. Conclusion: It could be concluded that; successful recognition of cerebral and uterine toxoplasmosis were sequential to the three T. gondii virulent types, and reflects the possible match of pathological and serological alters with humans at similar circumstance.